2016
DOI: 10.1007/s12035-016-0278-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate Provides Neuroprotection in Eclampsia-Like Seizure Model by Ameliorating Neuroinflammation and Brain Edema

Abstract: Eclampsia is a hypertensive disorder of pregnancy that is defined by the new onset of grand mal seizures on the basis of preeclampsia and a leading cause of maternal and fetal mortality worldwide. Presently, magnesium sulfate (MgSO) is the most effective treatment, but the mechanism by which MgSO prevents eclampsia has yet to be fully elucidated. We previously showed that systemic inflammation decreases the seizure threshold in a rat eclampsia-like model, and MgSO treatment can decrease systemic inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 64 publications
1
30
0
7
Order By: Relevance
“…On the basis of methods reported in the study of Fass et al [ 21 ] following the infusion of lipopolysaccharide (LPS), in our previous study intraperitoneal injection of PTZ was used to induce seizures [ 5 , 22 ]. In addition, we detected the biometric parameters of the two models; changes in blood pressure, and urinary albumin data were similar to the present study, and these two variables in the previous studies had the same time course.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of methods reported in the study of Fass et al [ 21 ] following the infusion of lipopolysaccharide (LPS), in our previous study intraperitoneal injection of PTZ was used to induce seizures [ 5 , 22 ]. In addition, we detected the biometric parameters of the two models; changes in blood pressure, and urinary albumin data were similar to the present study, and these two variables in the previous studies had the same time course.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the classical PE models (LPS infusion) established by Fass et al [ 21 ], we used intraperitoneal injection of PTZ (40 mg/kg body weight) to induce seizures to set an eclampsia-like model to be used in the subsequent studies in order to fully investigate the mechanisms underlying PE and E, and we would try to apply other models. By using PTZ-induced rat models, our previous studies suggested that excessive systemic inflammation and increased brain inflammation in pre-eclampsia decreased the eclampsia-like seizure threshold [ 22 , 39 ], and seizures further increased brain inflammation [ 5 ]. We also found that the number of activated microglia cells and astrocytes in the CA1 area was higher in the pre-eclampsia group than in the normal pregnancy group; this number continued to increase in the eclampsia group [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Nissl staining, paraffin-embedded sections of brain tissue (5-μm-thick) were stained with cresyl violet, as previously described [17]. Normal neurons had large bodies, round nuclei located in the central soma, and abundant cytoplasm.…”
Section: Methodsmentioning
confidence: 99%
“…Также доказано, что назначение сульфата магния при преждевременных родах значитель-но снижает риск развития кровоизлияния в мозг у недо-ношенного новорожденного [14]. Кроме того, изучено и показано нейропротекторное действие сульфата маг-ния с целью профилактики и лечения эклампсии у бере-менных женщин за счет предупреждения процессов нейровоспаления и отека головного мозга [15].…”
unclassified